Goodyear : navigating a socio-political firestorm - Brooks, Bradley; Powell, Gary E.; Berka, Gregory Charles (London : Society for Case Research, 2021)
The Goodyear Tire and Rubber Company was faced with a sitting president calling for a boycott of its products and growing consumer controversy. Social media posts displayed images approving Goodyear employee apparel supporting the Black Lives Matter social movement while banning apparel supporting Blue Lives Matter or President Trump. Since social media posts identified the image as having originated from Goodyear's corporate office, many consumers perceived these views as representative of the entire company. The images, however, originated from a local Kansas plant, not Goodyear corporate headquarters as portrayed on social media. Faced with consumer backlash and a presidential boycott request, Goodyear was forced to decide if, and how, to respond.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Goodyear Tire and Rubber Company -- Management -- Case studies; Boycotts -- Case studies